Comparison of compressed air energy storage process in aquifers and caverns based on the Huntorf CAES plant. (1st November 2016) - Guo, Chaobin; Pan, Lehua; Zhang, Keni; Oldenburg, Curtis M.; Li, Cai; Li, Yi
Highlights: A wellbore-reservoir coupled model is developed based on Huntorf CAES plant. Performance of CAESA can be similar to or even better than CAESC. The temperature of CAESA shows a smooth variation due to large grain specific heat. The impact of initial gas bubble volume on the storage efficiency is not significant. Boundary permeability of the reservoir can significantly affect total storage efficiency. Abstract: CAESA (compressed air energy storage in aquifers) attracts more and more attention as the increase need of large scale energy storage. The compassion of CAESA and CAESC (compressed air energy storage in caverns) can help on understanding the performance of CAESA, since there is no on running CAESA project. In order to investigate the detail thermodynamic process, integrated wellbore-reservoir (cavern or aquifer) simulations of CAES (compressed air energy storage) are carried out based on parameters of the Huntorf CAES plant. Reasonable matches between monitored data and simulated results are obtained for the Huntorf cavern systems in the wellbore and cavern regions. In this study, the hydrodynamic and thermodynamic behaviors of CAES in cavern and aquifer systems are investigated, such as pressure and temperature distribution and variation in both the wellbore and cavern regions of the CAES systems. Performances of CAESA are investigated with numerical models and compared with the performances of CAESC. The comparisons of CAESC and CAESA indicate that the pressure variation in CAESA shows a wider variation range than that in CAESC, while the temperature shows a smooth variation due to the large grain specific heat of the grains in the porous media. The simulation results confirm that the CAES can be achieved in aquifers, and further that the performance of energy storage in aquifers can be similar to or better than CAESC, if the aquifers have appropriate reservoir properties, which means the gas bubble can be well developed in an aquifer with such properties and the aquifer should have closed or semi-closed boundaries. The impacts of gas-bubble volume, formation permeability, and aquifer boundary permeability on storage efficiency are investigated and the simulation results indicate that the increase of gas bubble volume and permeability can improve the efficiency, but the effect is not significant. The gas bubble boundary permeability has a small effect on the energy efficiency of the sustainable daily cycle but can significantly affect total sustainable cycle times. The analysis of thermodynamic behaviors in CAESA suggests that more attention should be paid to the heat storage, reservoir properties and two-phase flow processes.